WORKERS OF THE WORLD, UN-UNITED: A DISCUSSION THROUGH A GENDERED LENS ON WHY STRONGER PROTECTION OF WORKERS IN THE INFORMAL ECONOMY WILL BETTER EQUIP SOUTH AFRICA TO COPE WITH LABOUR MARKET CHANGES OF THE FOURTH INDUSTRIAL REVOLUTION (The Pretoria Student Law Review, 2021)
This article will investigate the readiness for labour legislation to cater for the Fourth Industrial Revolution (4IR) by comparing the structure of the current labour market and that of the future, through a gendered perspective. There are two core protections that underpin employee entitlements and rights. The first is the formal recognition of an individual as an employee or worker, which is often formalised through an employment contract. Many South Africans are engaged with work in the informal sector which do not make them privy to most of those rights and entitlements. This is problematic when considering how vulnerable these individuals already are, and that black women are concentrated in this sector. The inadequate protection of informal workers is going to pose challenges for South Africa’s ability to cope with changes brought on by the Fourth Industrial Revolution and the projected shift towards labour flexibility and casualisation. The second is collective bargaining, which empowers other rights to be realised. Collective bargaining is framed through the use of trade unions as its primary mechanism. While they may have been relevant at the time of the Labour Relation’s Act’s (LRA) inception, they have become an inappropriate medium to further workers’ rights and are projected to continue to lose members in the near future, as organisation cannot happen as effectively with a decentralised workspace and an incoherent internal firm structure. I will conclude the piece by offering recommendations which encourage more progressive labour legislation that takes into account both the changing nature of work and the specific interests of women.
Keywords: labour legislation; readiness; Fourth Industrial Revolution; 4IR; formal recognition; employee or worker; collective bargaining